Matriz de Nossa Senhora da Conceição da Serra-ES : igreja e religiosidade no contexto da romanização católica (1880-1916) - Pimentel, Raquel Ramos (2012)
This dissertation aims to analyse the manifestations of religiosity related to the church of “Nossa Senhora da Conceição” in the city of Serra in Espírito Santo- Brazil, during the interventions of the bishops Pedro Maria de Lacerda, João Nery Batista Cor